RESIDUAL FORCE MINIMUM RANK UPDATE METHOD FOR DAMAGE IDENTIFICATION OF SPACE TRUSS STRUCTURES - JIANG Ge; FENG XiaoDong (Jixie qiangdu)
Based on the minimum rank damage identification method,a minimum rank update method is proposed to study the damage identification of space truss structures. The propose combines the residual force equation with the minimum rank update method by introducing the eigenvalue matrix,effectively dealing with the problem about the number of taken modes must be equal to the rank of the stiffness perturbation matrix,and ultimately solving the space truss structure damage location and damage degree by the minimum rank update method. A space truss structure is taken as an example to verify the minimum rank update method,and the influence of measurement noise is analyzed and discussed. The results show that the minimum rank update method is accurate and reliable,and has strong robustness.